Cover Picture: Glutamate Ionotropic Receptor Kainate Type Subunit 3 (GRIK3) promotes epithelial‐mesenchymal transition in breast cancer cells by regulating SPDEF/CDH1 signaling (Mol Carcinog 7/2019). Issue 7 (4th June 2019) - Xiao, Bin; Kuang, Zhenzhan; Zhang, Weiyun; Hang, Jianfeng; Chen, Lidan; Lei, Ting; He, Yongyin; Deng, Chun; Li, Weiwei; Lu, Jingrun; Qu, Jing; Zhou, Quan; et al.
Abstract : Back Cover Caption : The cover image is based on the Research Article Glutamate Ionotropic Receptor Kainate Type Subunit 3 (GRIK3) promotes epithelial‐mesenchymal transition in breast cancer cells by regulating SPDEF/CDH1 signaling by Bin Xiao et al., DOI 10.1002/mc.23014 .